Assessment of MICE Green Building Score Utilizing GREENSHIP Rating System: Value Engineering Approach - Sutikno, Sutikno; Hardjomuljadi, Surwono; Wiyanto, Henny (EPI International Journal of Engineering, 2024)
The building industry used for meetings, incentives, conventions, and exhibitions (MICE) is one of the industries that has high economic attractiveness for investors. Regulations and user requests for new buildings must meet environmentally friendly building standards. The GREENSHIP green building certification system is issued by the Green Building Council Indonesia. To obtain a platinum rating, a minimum total of 56 points requires additional investment costs but will result in operational cost savings. The purpose of this paper is to find out what factors influence the optimization of construction costs through value engineering to achieve a green building rating tool with optimum costs in MICE green building design. The findings show that energy is the most influential factor in obtaining platinum rating certification, so it requires value engineering to achieve optimal investment costs. The novelty of this research is that the selection of materials/machines and work methods for environmentally friendly concepts that save energy needs to be done from the start of design to achieve a payback period for the additional cost that can be returned in 3 years and 2 months. that is feasible for new investments, which can be a commitment for company owners to build MICE green buildings. Keywords: Green building; MICE; value engineering